Eurographics Workshop on Graphics and Cultural Heritage 2023: GCH23, Salento, Lecce, Italy, 4-6 September 2023 - Bucciero, A. (Eurographics Association, 2023)
The 21st Eurographics Workshop on Graphics and Cultural Heritage is taking place from 4th - 6th of September 2023 in Salento / Lecce, Italy.
Gesehen am 07.09.2023
Keywords: Konferenzschrift